Análise comparativa entre metodologias de otimização de portfólio - Caressato, Nathan José Lara [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Based on empirical observations of the investment profile of a Brazilian citizen, this paper aims to identify investment opportunities in the financial market, based on stocks, government bonds backed by the federal government and international currencies, allocated according to different methods, which are exchanged, forming 19 different portfolios, each different in the way each asset is allocated. The methods described are three different ones, such as Markowitz's Modern Portfolio Theory (1952), then a proposed Multi-Objective allocation proposed by Huang (2015) and finally portfolios created based on equidistribution of assets. In addition, a Data Envelopment Analysis (DEA) is also used for a more accurate filtering of the actions that compose the portfolios. A criterion is also used to measure the investor's risk appetite based on his or her age. The analysis showed that the portfolio composed of DEA-filtered shares and allocated according to Markowitz's TMP (1952), with equidistribution of securities and the application of Huang's Multi-Objective allocation (2015) for currencies presented higher results than other portfolios

Partindo de observações empíricas do perfil de investimento de um cidadão brasileiro comum, este trabalho tem por objetivo identificar oportunidades de investimento no mercado financeiro, baseado em ações, títulos públicos lastreados pelo governo federal e moedas internacionais, alocados segundo diferentes métodos, que se intercambiam, formando 19 portfólios diferentes, cada um diferente na forma que se aloca cada ativo. Os métodos descritos são três métodos diferentes, como a Teoria Moderna do Portfólio de Markowitz (1952), depois uma proposta de alocação Multi-Objetivo proposta por Huang (2015) e por fim portfólios criados com base na equidistribuição dos ativos. Além disso também é usada uma análise envoltória de dados (DEA) para uma filtragem mais apurada das ações que compõem os portfólios. Também é usado um critério para a mensuração do apetite ao risco do investidor com base em sua idade. As análises feitas mostram que o portfólio composto de ações filtradas pelo DEA e alocadas segundo a TMP de Markowitz (1952), com a equidistribuição dos títulos e a aplicação da alocação Multi-Objetivo de Huang (2015) para moedas apresentou resultados superiores aos outros portfólios em comparação
Comparative analysis between portfolio optimization methodologies
Keywords: Ações (Finanças); Investimentos; Risco (Economia); Stocks